Resource Management in Silvipastures in Shivaliks - Srivastva, A. K.; Misri, B.; Singh, B. (Indian Forester, 2003)
Silvipasture is one of the major farm enterprises of hilly ecosystem. The region spreads across 3.8 million ha in Jammu & Kashmir, Himachal Pradesh, Uttaranchal, Punjab and Haryana States in North-West Himalaya. More than 80% of the hills including Shivaliks are affected by soil erosion and land degradation, being highly fragile because of sub-tropical climate, steep slopes, heavy rainfall and shallow soil depth. Major causes of degradation could be due to natural factors, rising demands of fodder, poor management practces and policy factors. With livestock population far exceeding the carrying capacity, and severe degradation of pasturelands, there is a strong need for natural resource management in silvipastoral systems. Land degradation and productivity decline was found more acceptable to people in addition to erosion control. Silvipasture land use was recommended for land capability class IV, VI and VII lands. Staggered contour trenching in Kangra watersheds improved productivity due to better moisture regime and trapping as sediment. This reduced the soil erosion and improved productivity, survival of plants and output from silvipastoral system. Treatment with staggered contour trenches at 1 m vertical interval could create 227 to 424 m3/ha runoff retention and trapped 37 t/ha/yr silt in watersbeds in Kangra. Fragility of ecosystem is assigned to severe decline in soil organic carbon in 5-15 cm layer (0.54%), compared to rich top soil (1.32% in 0-5 cm depth of soil). Thus, it is expected to impart sustainability and prosperity to Shivalik silvipasture ecosystem.